Rational Calogero-Moser Model: Explicit Form and r-Matrix of the Second Poisson Structure - Avan, J.; Ragoucy, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
We compute the full expression of the second Poisson bracket structure for N=2 and N=3 site rational classical Calogero-Moser model. We propose an r-matrix formulation for N=2. It is identified with the classical limit of the second dynamical boundary algebra previously built by the authors.